PERAN KELUARGA DALAM PENCEGAHAN RISIKO JATUH PADA LANSIA DI WILAYAH PUSKESMAS JONGAYA MAKASSAR - Erlina Y Kongkoli; Baharuddin, Baharuddin; Syallomitha Baso (Bajang Institute, 2024)
Currently, Indonesia still pays little attention to the safety of the elderly, even though the safety and health of the elderly are two important things that are interconnected, healthy elderly people who do not behave well can fall. Falls are caused by 2 factors, namely intrinsic and extrinsic factors. The consequences of falls are not light, such as head injuries, soft tissue injuries, and even bone fractures. Because the elderly face serious health problems and the quality of life begins to decline, families have a big role in preventing the risk of falls, namely by knowing the factors that cause falls in the elderly. The aim of the research is to understand the role of the family as educators, motivators and facilitators in preventing the risk of falls in the elderly in the Jongaya Makassar Community Health Center area. This research uses a type of qualitative research that uses an in-depth interview approach through a question and answer process to obtain information. The number of cases in this study were 2 families who had elderly people living in the same house with risk factors for falls such as age, being sick or having a history of illness, the use of assistive devices to support life, activities, home and environmental conditions. This research was conducted in the Jongaya Makassar community health center area. The results of this research show that the role of the family as a motivator plays a good role, families who always motivate the elderly and look after the elderly in their daily lives can have a good impact on preventing the risk of falls in the elderly. Then the role of the family as an educator also plays a good role, the family always provides education to the elderly so that the elderly can know how to prevent the risk of falling. and the role of the family as a facilitator in this research did not play a good role. Families cannot provide assistive equipment to support the lives of elderly people due to several limitations. The researcher concluded that the family's role as a motivator and educator played a good role, but the family's role as a facilitator did not play a good role because they were unable to facilitate the elderly with assistive devices, so the researcher suggested to the family to modify the environment to keep it safe. This method can minimize the risk of falls in the elderly